Risedronate does not reduce mechanical loading-related increases in cortical and trabecular bone mass in mice. - Sugiyama, T; Meakin, L; Galea, G; Jackson, B; Lanyon, L; Ebetino, F; Russell, R; Price, J (2011)
To establish whether the combination of anti-resorptive therapy with mechanical loading has a negative, additive or synergistic effect on bone structure, we assessed the separate and combined effects of risedronate and non-invasive dynamic loading on trabecular and cortical bone. Seventeen-week-old female C57BL/6 mice were given daily subcutaneous injections of vehicle (n=20) or risedronate at a dose of 0.15, 1.5, 15 or 150 μg/kg/day (n=10 in each) for 17 days. From the fourth day of treatment, the right tibiae were subjected to a single period of axial loading (40 cycles/day) for three alternate days per week for two weeks. The left tibiae were used as internal controls. Trabecular and cortical sites in the tibiae were analyzed by high-resolution micro-computed tomography and imaging of fluorochrome labels. In the non-loaded tibiae, treatment with the higher doses of risedronate at 15 or 150 μg/kg/day resulted in higher trabecular bone volume and trabecular number than in vehicle-treated controls, whereas such treatment was associated with no differences in cortical bone volume at any dose. In the loaded tibiae, loading induced increases in trabecular and cortical bone volume compared with contra-lateral controls primarily through increased trabecular thickness and periosteal expansion, respectively, independently of risedronate treatment. In conclusion, the response to mechanical loading in both trabecular and cortical bone in mice is therefore not impaired by short-term treatment with risedronate, even over a 1000-fold dose range. In considering the optimization of treatments for osteoporosis, it is reassuring that anti-resorptive therapy and mechanical loading can exert independent beneficial effects.